Evaluation of load losses in the ventilation circuit by the use of fortification in coal mines, study case: nechí mine, amagá, antioquia (2014)
The research aims to identify the variables which influence on the increase of risk for explosions in underground coal mines, especially in the accumulation of coal dust on top of the fortification, as well as analyze how these affect the load losses in the ventilation circuit and the proper evacuation of coal dust. This analysis was carried out by a guide field visits to Nechí Mine (Municipality Amagá, Antioquia) where it was observed that the coal dust accumulated significantly in the wooden doors that in the steel arches, we proceeded to simulate different geometries of fortification and the amount of these for the purpose to determine which is the geometry that contributes to reducing the load losses. After analyzing the different scenarios, the geometry that optimizes the ventilation circuit has been called geometry Circular 2, which shows reduction in load losses of up to 14.67% compared to other geometries analyzed under the same conditions. Whit this, are proposed alternatives more efficient to optimize the ventilation circuit and ensure health and safety conditions for workers inside the mine.